Oxysterole-binding protein targeted by SARS-CoV-2 viral proteins regulates coronavirus replication - Ma-Lauer, Yue; Li, Pengyuan; Niemeyer, Daniela; Richter, Anja; Pusl, Konstantin; von Brunn, Brigitte; Ru, Yi; Xiang, Chengyu; Schwinghammer, Sebastian; Liu, Jia; Baral, Priya; Berthold, Emilia J.; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Oxysterol-binding protein (OSBP) functions as a critical lipid transporter, facilitating the exchange of cholesterol between the Golgi apparatus and endoplasmic reticulum membranes.We show that OSBP plays a critical role in the positive regulation of coronavirus replication. In addition, we introduce a novel OSBP-binding compound, ZJ-1, which reduces OSBP levels and exhibits potent antiviral effects against several coronaviruses, including SARS-CoV-2. Through our investigation, we identified the SARS-CoV-2 non-structural proteins Nsp3, Nsp4, and Nsp6as key interactors with OSBP, particularly involved in double-membrane vesicle formation. In addition, Nsp3 a.a.1-1363, Nsp4, and Nsp6 target vesicle-associated membrane protein (VAMP)-associated protein B (VAP-B), a critical factor in anchoring OSBP to the ER membrane.Notably, the interaction between OSBP and VAP-B is substantially disrupted by Nsp3 a.a.1-1363 and partially impaired by Nsp6. Furthermore, SARS-CoV-2 orf7a, orf7b, and orf3a were identified as additional OSBP targets, with OSBP contributing to their stabilization. Our findings highlight OSBP as a promising target for the development of antiviral therapies against SARS-CoV-2 and other coronaviruses.